The floristics and community structure of mangroves in Antique Province, Panay Island, Philippines - Sansait, May M (Miagao, Iloilo University of the Philippines Visayas, 2011)
This study assessed the community structure of mangroves in 15 municipalities in the Province of Antique, Philippines. Mangrove areas were evaluated in terms of a) species composition, b) stand basal area, c) stems per hectare, d) relative density, e) relative frequency, f) relative dominance, g) association, h) seedling and sapling density. In addition, selected physical and chemical factors such as salinity, pH, and temperature for water and soil were also determined. Mangrove stands in the Antique Province are in small ptches along the strems, river mouth and tributaries mostly situated away from strong wavees and high winds with the accumulated silt from upland necessary for mangrove colonization and growth. GPS-assisted surveys reveal that the Province of antique has a total mangrove area of 309.511 hectares of which the Island of Semirara, Claya contributed the largest mangrove cover at 95.006 hectares. The Municipality of Hamtic has the largest pond area of 277.734 hectares with only 38.958 hectares mangrove cover giving ration of 0.14.1 which is low, beyond the recommended mangrove-to-pond ratio of 4:1 necessary for maintaining a healthy and productive mangrove ecosystem. The mangroves in Hamtic had the highest Index of density at H'= 1.08 while Belison had the lowest at H'=0.24 only. Equitability among species recorded was highest in Sebaste at J'=0.97 while it was least at Caluya with J'=0.59 only. Libertad mangroves had the highest stand basal area at 29.74 m2/ha2 whlle the least was recorded at Bugasong with only 0.57m2/ha2. Although Nypa fruticans is the most abundant mangrove species. Sonneratia ovata (93.36 IV), Sonneratia alba (89.39 IV), Lumnitzera racemosa (71.36 IV) and Avicennia marina (65.16 IV) were the most important species while Aegiceras floridum (0.90 IV) was the least important. Observable factors that contributed to the loss of mangroves include utilization for construction of houses, fences, fish cage, firewood, charcoal, clearing of mangrove forest area for fishponds, salt ponds, piers, and reclamation area for airship, housing project as well as conversion into industrial zone.
Thesis (M.S. Biology.) -- Miagao, Iloilo : University of the Philippines Visayas, July 2010.
Keywords: Mangroves -- Antique Province, Philippines